Предмет: Математика, автор: sharlotkaa

1/(√17-4) - 1/(√17+4)

можете дать развёрнутый ответ? кто решит-тот молодец!

Ответы

Автор ответа: axatar
16

Ответ:

8

Пошаговое объяснение:

\tt \displaystyle \frac{1}{\sqrt{17} -4}- \frac{1}{\sqrt{17} +4} = \frac{1 \cdot (\sqrt{17} +4)}{(\sqrt{17} -4)\cdot (\sqrt{17} +4)}- \frac{1 \cdot (\sqrt{17} -4)}{(\sqrt{17} +4)\cdot (\sqrt{17} -4)} = \\\\= \frac{\sqrt{17} +4}{(\sqrt{17})^2 -4^2}- \frac{\sqrt{17} -4}{(\sqrt{17})^2 -4^2} = \frac{\sqrt{17} +4}{17 -16}- \frac{\sqrt{17} -4}{17 -16} =\\\\ =\frac{\sqrt{17} +4}{1}- \frac{\sqrt{17} -4}{1} =\sqrt{17} +4-(\sqrt{17} -4)=\sqrt{17}+ 4-\sqrt{17} +4=8

Похожие вопросы
Предмет: Математика, автор: Настя21438